2017
DOI: 10.1091/mbc.e16-12-0818
|View full text |Cite
|
Sign up to set email alerts
|

Core engagement with β-arrestin is dispensable for agonist-induced vasopressin receptor endocytosis and ERK activation

Abstract: For a prototypical GPCR, the human vasopressin receptor type 2 (V2R), βarr1 can form a stable complex associated via only the phosphorylated carboxyl terminus of the receptor. Such a partially engaged complex is functionally competent with respect to supporting receptor internalization and ERK MAPK activation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
89
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(93 citation statements)
references
References 40 publications
4
89
0
Order By: Relevance
“…Active conformation of the receptor and subsequent GRK-mediated phosphorylation are generally thought to be prerequisite for β-arrestin binding (16), suggesting that the two main interactions occur simultaneously. Recent studies have shown that the phosphate and the core interactions can be separated in vitro or by using receptor chimeras and mutants (51)(52)(53). However, the question remained whether the distinct interactions could be independent in physiologically relevant situations.…”
Section: Discussionmentioning
confidence: 99%
“…Active conformation of the receptor and subsequent GRK-mediated phosphorylation are generally thought to be prerequisite for β-arrestin binding (16), suggesting that the two main interactions occur simultaneously. Recent studies have shown that the phosphate and the core interactions can be separated in vitro or by using receptor chimeras and mutants (51)(52)(53). However, the question remained whether the distinct interactions could be independent in physiologically relevant situations.…”
Section: Discussionmentioning
confidence: 99%
“…All of the above findings fit with an emerging model whereby GPCRs affect multiple modes of β-arrestin function through interactions at functionally distinct sites. 93,94 Notably, the dependence of ERK1/2 activation on lengthened endocytic lifetimes has so far been demonstrated only with receptors whose activation of MAPK is dependent on β-arrestin.…”
Section: Signaling Consequences Of Receptor-regulated Endocytosismentioning
confidence: 99%
“…core-engaged) receptor-βarr complexes, respectively. As recent studies have revealed distinct functional outcomes associated with these two conformations of receptor-βarr complexes (Cahill et al, 2017; Kumari et al, 2016; Kumari et al, 2017; Sente et al, 2018), we envisioned that key determinants of the functional divergence of βarr isoforms may lie at the level of structural and conformational differences between receptor-bound βarrs.…”
Section: Introductionmentioning
confidence: 99%